Bacterial Profiles and Inflammatory Markers in Pregnancy-Related Urinary Tract Infections: Profil Bakteri dan Marker Peradangan pada Infeksi Saluran Kemih yang Berkaitan dengan Kehamilan - Layth Hussein Hadi Alshaibah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Urinary tract infections are among the most frequent bacterial infections occurring during pregnancy and may progress from mild lower tract involvement to severe renal complications. Specific Background: Inflammatory markers such as white blood cells, C-reactive protein, proteinuria, red blood cells, and procalcitonin are associated with infection severity but remain underexplored in regional clinical settings. Knowledge Gap: Limited data exist regarding the bacterial distribution and inflammatory marker patterns among pregnant women with UTIs in Al-Diwaniyah City. Aims: This study aimed to identify causative bacteria and assess inflammatory markers in pregnant women diagnosed with urinary tract infections. Results: A cross-sectional analysis of 140 pregnant women revealed significant variation in UTI severity across gestational ages, with mild cases predominating in the first trimester and more severe cases in later stages. The highest inflammatory marker levels were observed in very severe infections. Escherichia coli was the most frequently isolated pathogen (55%), followed by Klebsiella, Proteus, Pseudomonas, Enterobacter, and Citrobacter. Novelty: The study integrates bacterial profiling with inflammatory marker assessment to describe severity patterns during pregnancy. Implications: These findings support the use of inflammatory markers as indicators of UTI severity and contribute region-specific data for maternal infection management. Keywords: Urinary Tract Infection, Pregnancy, Inflammatory Markers, Bacterial Pathogens, Gestational Age Key Findings Highlights: Disease severity varied significantly across pregnancy trimesters. Severe cases showed markedly elevated inflammatory marker levels. Gram-negative bacteria dominated infection profiles among participants.